Impact of High-Pressure Homogenization on Enhancing the Extractability of Phytochemicals from Agri-Food Residues - Annachiara Pirozzi; Francesco Donsì (Molecules, 2023)
The primary objective of the Sustainable Development Goals is to reduce food waste by employing various strategies, including the reuse of agri-food residues that are abundantly available and the complete use of their valuable compounds. This study explores the application of high-pressure homogenization (HPH), an innovative nonthermal and green treatment, for the recovery of bioactive compounds from agri-food residues. The results demonstrate that the optimized HPH treatment offers advantages over conventional solid/liquid extraction (SLE), including shorter extraction time, solvent-free operation, low temperatures, and higher yields of phenol extraction (an approximately 20% improvement). Moreover, the micronization of agri-food residue-in-water suspensions results in a decrease in the size distribution to below the visual detection limit, achieved by disrupting the individual plant cells, thus enhancing suspension stability against sedimentation. These findings highlight the potential of HPH for environmentally friendly and efficient extraction processes.